ANALISIS KADAR OKSALAT PADA DUA JENIS TANAMAN KALE (Brassica oleracea var. acephala dan Brassica oleracea var. palmifolia ) DENGAN METODE SPEKTROFOTOMETRI UV - Emma Emawati; Deden Indradinata; Dina Yulia Agustina (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
Vegetables have an important function for metabolic and physiological processes in the body. Kale is dubbed as a super food because it has great health benefits. Kale contains nutrients such as vitamins A, C, potassium, calcium, iron, and manganese. Although vegetables have a lot of nutritional content, they also contain anti-nutrients, one of which is oxalic acid. Oxalic acid can irritate the intestines and can be fatal if taken in high doses, so it should be limited to 0.60-1.25 g per day. The purpose of this study was to determine the levels of oxalate in kale by UV spectrophotometry method measured at a wavelength of 351 nm. The product of the reaction is I3 which is proportional to the oxalate concentration. This research begins with method validation. The results of the validation of the calibration curve analysis method have a regression line equation y = 0.4943x + 0.244 with a correlation coefficient 0.998. The detection limit and quantization limit are 0.4018 and 1.3395. The coefficient of variance is 0.8180 and the percent recovery is 89, 92 and 101%. The results of this study showed that the oxalate content in curly kale was 0.6911 mg/100g and kale nero was 1.7045 mg/100g.